Physicochemical composition of Tamarindus indica L. (Tamarind) Fruits in the agro-ecological zones of Uganda - Okello, Jaspher; Okullo, John B. L.; Eilu, Gerald; Nyeko, Philip; Obua, Joseph (Food Science & Nutrition, 2018)
The relationships between the physicochemical composition of Tamarindus indica pulp and seeds, and agro-ecological zones and land use types were assessed in Uganda. The objective was to determine the relationship between the physicochemical composition, agro-ecological zones, and land use types. The samples were processed by manually depulping the T. indica pods, sun-drying the pulp and seeds, and grinding into powder. The powdered samples were analyzed for β-carotenoids, vitamin C (ascorbic acid), calorific value, crude oil, acid, and peroxide values. Data were analyzed using ANOVA in the general linear model (GLM). Principal component analysis (PCA) was used to relate the physicochemical properties to the agro-ecological zones and land use types. There were significant differences (p ≤ .05) in the physicochemical composition variables between agro-ecological zones and land use types. Land use types showed strong correlations with physicochemical properties while agro-ecological zones did not show correlations. The results show that in terms of general properties, T. indica pods provide a valuable, rich, and exceptional source of vitamin C, compared to many widely consumed indigenous and conventional fruits and vegetables. The pods from land use types characterized by natural habitats had relatively more nutrient levels than the land use types influenced by anthropogenic activities.
Keywords: agro-ecological zones, land use types, on-farm, physicochemical composition, tamarind, Tamarindus indica